Comparative Study of Responsible Tourism Trough Pro-Poor Tourism Approach in Kali Gajahwong Tourism Village and Code Tourism Village - Nisa, An Nuur Khairune; Fadin, Delfyan Intan Nurmala (Journal of Tourism Education, 2023)
This study aims to determine the comparison of community responsibility in Code Tourism Village and Kali Gajahwong Tourism Village with a pro-poor tourism (PPT) approach. The two tourist villages started as a slum riverbank area and then turned into a tourist destination. The method used is a qualitative descriptive method with data collection through observation, literature study, and in-depth interview.  The results of the study showed  differences in the degree of responsibility of people living in Code and Kali Gajahwong tourism villages from PPT perspective to achieve sustainable tourism. Nonetheless, the two tourist villages practice responsible tourism by prioritizing the interests of the environmental ecosystem while preserving the existence of local culture. The PPT approach reveals that there are differences in the degree of independence, the number of tourist visits, utilization of technology, and the psychological conditions of local communities when implementing tourism activities in Kali Gajah Wong and Code.